High-temperature oxidation behavior of laser-aided additively manufactured NiCrAlY coating. (April 2017) - Ansari, M.; Shoja-Razavi, R.; Barekat, M.; Man, H.C.
Graphical abstract: Highlights: NiCrAlY coatings were additively manufactured through a laser-aided process. The additively manufactured coatings had γ/β dendritic structure. The coatings showed a good oxidation resistance at 1200 °C. The oxide scale formed on the coatings consisted of Al2 O3 and Al5 Y3 O12 oxides. Abstract: In this study, NiCrAlY coatings were additively manufactured on the surface of IN738 substrate through a laser-aided additive manufacturing approach. The high-temperature oxidation behavior of freestanding coatings at 1200 °C was also investigated. The coatings were thick, dense, and well-bonded with dendritic γ/β microstructure. The results proved that the coatings were able to withstand the operating temperature of 1200 °C for up to ten cycles. After ten cycles of oxidation, the oxide scales formed on the coatings were mainly composed of α-Al2 O3 and Al5 Y3 O12 phases; however, NiO, Cr2 O3 and Ni(Cr, Al)2 O4 phases were not detected.